Penerapan Kurikulum Merdeka di Kelas XI SMA Negeri 8 Samarinda Tahun Ajaran 2023/2024 - Adam Kholiq; H. Asnar; Jamil Jamil (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to describe the Implementation of the Merdeka Curriculum in Class XI of SMA Negeri 8 Samarinda in the 2023/2024 Academic Year, to find out what are the inhibiting factors in the implementation of the Merdeka Curriculum in Class XI of SMA Negeri 8 Samarinda and to find out efforts to overcome obstacles in the Implementation of the Merdeka Curriculum in Class XI of SMA Negeri 8 Samarinda. Descriptive qualitative research type. This research was conducted at SMA Negeri 8 Samarinda in February 2024-March 2024. The research subjects were the Deputy Principal for Curriculum, P5 Supervising Teacher, and 4 students using interview, observation, and documentation techniques. Data analysis techniques are data collection, data reduction, data presentation, data collection and data conclusion. The results showed that the implementation of the curriculum in Class XI of SMA Negeri 8 Samarinda in the 2023/2024 academic year shows a structured process starting from the selection of driving schools to teacher training, with comprehensive learning planning as the main foundation.Related inhibiting factors in the implementation of the Merdeka Curriculum in Class XI of SMA Negeri 8 Samarinda are Resources and Student Participation The solution to inhibiting factors is to improve the learning environment and social support. The learning environment that needs to be designed is flexible with an emphasis on project-based learning and the use of digital technology. Improving infrastructure, classroom quality and teacher training are important steps that need to be taken. Social support includes counseling services, mental health programs, collaboration between teachers, students, and parents in presenting inclusive learning and providing extracurricular programs and fair access to school resources for all students aims to create independent, creative, and adaptive students. With the commitment and cooperation of various parties, success in implementing the Merdeka Curriculum will be realized.